Pengaruh inisiasi menyusui dini terhadap pencegahan hipotermia pada bayi baru lahir (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background : Hypothermia is one of the causes of mortality and morbidity in newborns. Early initiation of breastfeeding is a simple intervention that can significantly improve neonatal outcomes, namely reducing the risk of neonatal death, increasing affection, increasing breastfeeding duration, stabilizing body temperature, stabilizing the baby's breathing, pulse and blood glucose.Objective: To determine whether early initiation of breastfeeding has an effect on the prevention of hypothermia in newborns at the cipamokolan health center.Methods: This study uses a method based on evidence based case reports. That is research conducted based on literature search in several articles. The articles he used were taken from several sources, namely Google Scoolar, Cochrane and Pubmed. Then evidence based is carried out directly on cases that occur at the Cipamokolan Health Center.Results: After reviewing 3 journals, it was found that early initiation of breastfeeding can be used as a prevention of hypothermia in newborns. Early initiation of breastfeeding can increase the body temperature of the newborn. After being carried out in the case, it was found that Mrs. R's baby had an increase in body temperature of 0.1 oC and the baby did not experience hepothermia.